British experience for modern corporate law in Ukraine - Nahorniak, Iryna; Нагорняк, Ирина; Нагорняк, Ірина (Одеса : Фенікс, 2015)
System crisis in Ukraine, which accompanies all fields of human life, leads to the search for ways and mechanisms in order to minimize losses of group of interests. The author describes the basic mechanisms of English law, which are effectively carried out in Ukrainian legal field. It was revealed and justified the necessity of improvement of the national legislation by implementing provisions on noncompetition and performance guarantees.
Nahorniak I. British experience for modern corporate law in Ukraine / I. Nahorniak // Актуальні проблеми політики зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2015. – Вип. 56. – С. 291-295.
Keywords: системна криза в Україні; англійське право; внесення положень про неконкуренцію і гарантій виконання зобов’язань; системный кризис в Украине; английское право; внесения положений о неконкуренции и гарантий выполнения обязательств; system crisis in Ukraine; English law; implementing provisions on noncompetition and performance guarantees